Rapid‐access cardiology services: can these reduce the burden of acute chest pain on Australian and New Zealand health services?. Issue 9 (September 2017) - Klimis, Harry; Thiagalingam, Aravinda; Altman, Mikhail; Atkins, Emily; Figtree, Gemma; Lowe, Harry; Cheung, Ngai Wah; Kovoor, Pramesh; Denniss, Alan Robert; Chow, Clara K.
Abstract: Chest pain is common and places a significant burden on hospital resources. Many patients with undifferentiated low‐ to intermediate‐risk chest pain are admitted to hospital. Rapid‐access cardiology (RAC) services are hospital co‐located, cardiologist‐led outpatient clinics that provide rapid assessment and immediate management but not long‐term management. This service model is described as part of chest pain management and the National Service Framework for coronary heart disease in the United Kingdom (UK). We review the evidence on the effectiveness, safety and acceptability of RAC services. Our review finds that early assessment in RAC outpatient services of patients with suspected angina, without high‐risk features suspicious of an acute coronary syndrome, is safe, can reduce hospitalisations, is cost effective and has good medical practitioner and patient acceptability. However, the literature is limited in that the evaluation of this model of care has been only in the UK. It is potentially suited to other settings and needs further evaluation in other settings to assess its utility.